Three interesting fungi from American bullfrog larvae (Rana catesbeiana) in Yunnan, China - Yang, Erfu; Lu, Wenhua; Tibpromma, Saowaluck; Dai, Dongqin; Gao, Ying; Promputtha, Itthayakorn; Karunarathna, Samantha C. (Phytotaxa, 2023)
American bullfrog (Rana catesbeiana) is an alien invasive species in southwest China native to the central and eastern United States and southeastern Canada. After the 19th century, they extensively appear in aquaculture and natural environments worldwide as a delicious food but also creating a serious threat to the survival and development of native species. In the early rainy season, dead American bullfrog larvae floating on the water of unnamed ponds in Qujing Normal University, Yunnan Province, China were collected and brought to the mycology laboratory, and three interesting fungal strains were isolated from their intestinal contents. Phylogenetic analyses were carried out on the resultant isolates based on multiple gene sequences (ITS, LSU, rpb2, tub2, tef1-α), and results confirmed that the three strains belong to three species, namely; Boothiella tetraspora, Sordaria macrospora and Trichoderma virens. The morphological characteristics were also used to describe the fungal taxa. Photographic plates, descriptions, and phylogenetic trees that show the placements of the fungal species are reported herein.